O movimento zapatista e a solidariedade de classe transnacional: uma análise da luta de classes na globalização - Demuner, Davi Matias Marra (2017)
The global hegemony exercised by the Transnational Capitalist Class (TCC), by disciplining neoliberalism worldwide as a model of economic development, imposes various ideological and material barriers to the construction of new political, economic and social organization forms, which threaten, above all, the concentration of capital accumulation. It is then necessary to reflect on organized forms of collective action capable of mobilizing a correlation of forces favorable to social development to the detriment of the capitalist game. The route adopted by the Mexican state demonstrates the nodal convergence of domestic interests from political society of the Mexican State with the disciplinary development agenda imposed by the organic core of capitalism under the concept of globalization, and since then the Mexican economy has reorganized to be adequate to standards required. In southern Mexico, the EZLN rebels against the passive revolution of the Mexican state and it builds from below an alternative of direct democracy through autonomy, which can be read as a passive antirevolution activity. As a result of this struggle process for self-government, it emerges the Zapatista transnational solidarity network, in which other social movements and actors of international civil society participate by assisting local Zapatista projects and in the international struggle against a globalization from above. However, this mobilization of transnational social forces does not occur without controversy, such as the role of technology by actors in resistance, deterritorialization of the struggle objectives and the recurrent practice of transformismo from hegemony.